Clinical characteristics and management of 106 patients with pyogenic liver abscess in a traditional Chinese hospital - Nie, ShiJiao; Lin, Da; Li, XiaoWen (Frontiers in Surgery, 2023)
This study was a retrospective analysis of 106 patients with pyogenic liver abscesses, who were managed in a traditional hospital in China over the past eight years. The study aims to provide evidence to improve current diagnosis and corresponding treatment strategies for pyogenic liver abscess. Patients treated at the Guangxing Hospital, which is affiliated to the Zhejiang Traditional Chinese University, Hangzhou, were included and their basic features, clinical manifestations, laboratory features, imageology features, and outcomes were analyzed retrospectively. Diabetes mellitus (45.3%, 48/106), biliary calculi (36.8%, 39/106), and history of abdominal surgery (15.1%, 16/106) were the three most common risk factors leading to PLA. Fever and chills (95.3%, 101/106), right upper quadrant pain/epigastric discomfort (68.9%, 73/106), nausea and vomiting (38.8%, 41/106), and cough and sputum (14.2%, 15/106) were the most common clinical manifestations. For most patients, the abscesses were located in the right liver. The most commonly found bacteria were Klebsiella pneumoniae (54.8%, 42/76), Escherichia coli (35.1%, 27/76), and Streptococcus pneumoniae (3.9%, 3/76). Liver Doppler ultrasound is a conventional and effective method to identify liver abscesses. Percutaneous puncture under B-ultrasound guidance was the most commonly used treatment. Of the included patients, 104 (98.1%) were cured, and one patient (0.9%) died. One patient was discharged due to multiple abscesses post treatment.